2016
DOI: 10.1002/jcp.25432
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Sequential Docetaxel Followed by High‐Dose Epirubicin in Combination With Cyclophosphamide Administered Concurrently With Trastuzumab. The DECT Trial

Abstract: To report the results of the DECT trial, a phase II study of locally advanced or operable HER2-positive breast cancer (BC) treated with taxanes and concurrent anthracyclines and trastuzumab. Eligible patients (stage IIA-IIIB HER2-positive BC, 18-75 years, normal organ functions, ECOG 1, and left ventricular ejection fraction (LVEF) !55%) received four cycles of neoadjuvant docetaxel, 100 mg/m 2 intravenously, plus trastuzumab 6 mg/kg (loading dose 8 mg/kg) every 3 weeks, followed by four 3-weekly cycles of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In a phase II clinical trial exploring efficacy and toxicity outcomes of the combined use of epirubicin and trastuzumab in 45 HER2-positive breast cancer patients with locally advanced operable disease, we observed better outcomes in patients with BMI25 and whose tumors did not express hormone receptors. 10 Beyond the not negligible differences in terms of patients characteristics, disease features and study design, these findings are fully consistent with what reported in the study herein presented. Conversely, in young breast cancer patients, i.e., women aged 45 or less, treated with neoadjuvant CT, we observed that lower values of BMI were associated with longer OS, along with non-TN molecular subtype and adjuvant RT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a phase II clinical trial exploring efficacy and toxicity outcomes of the combined use of epirubicin and trastuzumab in 45 HER2-positive breast cancer patients with locally advanced operable disease, we observed better outcomes in patients with BMI25 and whose tumors did not express hormone receptors. 10 Beyond the not negligible differences in terms of patients characteristics, disease features and study design, these findings are fully consistent with what reported in the study herein presented. Conversely, in young breast cancer patients, i.e., women aged 45 or less, treated with neoadjuvant CT, we observed that lower values of BMI were associated with longer OS, along with non-TN molecular subtype and adjuvant RT.…”
Section: Discussionsupporting
confidence: 91%
“…7 In light of the evidence emerged from recent literature and within our previously established research pipeline on the role of anthropometric and metabolic determinants of treatment efficacy in breast and ovarian cancer, we have now focused on a more restricted subgroup of patients from the original cohort with available data on body mass index (BMI) values at baseline assessment. [8][9][10][11][12][13][14][15] In this patient subgroup, data on several patient-and disease-related features were also analyzed and reinterpreted in light of the evidence emerging from the BMIrelated analysis. This study was designed and implemented within a real world setting.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study by Dawood et al in this same setting confirmed this outcome also in patients having received standard duration of trastuzumab [45]. A recent Italian phase II trial also explored the use of trastuzumab concomitantly to taxane and anthracycline treatment in the neoadjuvant setting, showing no increase in the rates of clinically overt HF and higher percentage of pCR than usually reported in trials assessing consecutive administration of these agents [46]. All these studies reported a reversible and rapidly recovering LVEF values in most of the cases.…”
Section: Discussionmentioning
confidence: 74%
“…However, previous studies did not conducted subgroup analysis for efficacy of the concurrent use of trastuzumab and anthracyclines, corresponding pCR rates and toxic effects were not reported. Considering the cardiotoxicity of both trastuzumab and anthracyclines, the concurrent use of trastuzumab and anthracycline-based NAC for HER2-positive breast cancer patients should be more careful 23 - 25 . Several randomized studies 10 - 14 had evaluated the efficacy and toxic effects of the concurrent use of trastuzumab and anthracycline-based NAC for HER2-positive breast cancer, thus we performed this meta-analysis to make a further study.…”
Section: Discussionmentioning
confidence: 99%